An investigation of reactivity effect due to inadvertent filling of the irradiation channels with water in NIRR-1 Nigeria Research Reactor-1. (May 2017) - Iliyasu, U.; Ibrahim, Y.V.; Umar, Sadiq; Agbo, S.A.; Jibrin, Y.
Abstract: Investigation of reactivity variation due to flooding of the irradiation channels of Nigeria Research Reactor (NIRR-1) a low power miniature neutron source reactor (MNSR) located at the Centre for Energy Research and Training, Ahmadu Bello University, Zaria Nigeria using the MCNP code for High Enrich Uranium (HEU) and Low Enrich Uranium (LEU) core has been simulated in this present study. In this work, the excess reactivity worth of flooding HEU core for 1 inner, 2 inner, 3 inner, 4 inner and all inner are 0.318 mk, 0.577 mk, 0.318 mk, 1.204 mk and 1.503 mk respectively, and outer irradiation channels are 0.119 mk, 0.169 mk, 0.348 mk, 0.438 mk and 0.418 mk respectively, the highest excess reactivity result from flooding both inner and outer irradiation channels is 2.04 mk ( ± 1.72 × 10 −7 ), the excess reactivity for LEU core was 0.299 mk, 0.568 mk, 0.896 mk, 1.195 mk and 1.524 mk in the inner irradiation channels, and the outer irradiation channels are 0.129 mk, 0.189 mk, 0.219 mk, 0.269 mk and 0.548 mk where the highest excess reactivity was 1.942 mk ( ± 1.64 × 10 −7 ) resulting from flooding inner and outer irradiation channels. The reactivity induced by flooding of the irradiation channels of NIRR-1 with water is within design safety limit enshrined in Safety Analysis Report of NIRR-1. The results also compare well with literature. Highlights: Investigation of reactivity due to flooding NIRR-1 irradiation channels. The highest excess reactivity result from flooding irradiation channels is 2.04 mk ( ± 1.72 × 10 −7 ). The excess reactivity in the inner and outer irradiation channels are in good agreement with bench mark result.